2021
DOI: 10.1530/eje-21-0075
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic characteristics in patients under 30 years with sporadic pituitary adenomas

Abstract: Objective: Pituitary adenomas (PA) are rare in young patients and additional studies are needed to fully understand their pathogenesis in this population. We describe the clinical and genetic characteristics of apparently sporadic PA in a cohort of young patients. Design: Clinical and molecular analysis of 235 patients (age ≤30 years) with a PA. Clinicians from several Spanish and Chilean hospitals provided data. Methods: Genetic screening was performed via next-generation sequencing and comparative genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
1
10
1
Order By: Relevance
“…Regarding pituitary neoplasms, up to now, some cases of these tumours were described in patients with MEN4 (43%) [12,38,45,47,49,50,52,53]. These findings agree with the estimated prevalence of pituitary tumours in patients with MEN1 (40%).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Regarding pituitary neoplasms, up to now, some cases of these tumours were described in patients with MEN4 (43%) [12,38,45,47,49,50,52,53]. These findings agree with the estimated prevalence of pituitary tumours in patients with MEN1 (40%).…”
Section: Discussionsupporting
confidence: 81%
“…However, the clinical course of patients affected by mutations in CKDIs is still poorly understood since few cases have been reported until now. We reviewed medical literature and genetic databases (ClinVar, HGMD) and found that a few more than 100 cases with MEN4, including 52 different variants of CDKN1B, have been reported to date [12,16,20,29,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. As supplementary material, we added a table with the total number of CDKIs pathogenic/likely pathogenic/VUS germline variants thus far reported along with the type of parathyroid lesion or other tumours found (if reported) and pathogenicity level of the variants, which was assessed following the ACMG guidelines [26] (see supplementary material Appendix 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolactinoma in a paediatric patient should raise suspicion for the presence of germline MEN1 and AIP mutations 159 . Pituitary adenomas with these mutations could have a more aggressive behaviour than those without 160 (see Supplementary Box 7).…”
Section: Consensus Statementmentioning
confidence: 99%
“…In a sporadic cohort of patients diagnosed with macroadenomas ≤30 years or with pituitary adenomas ≤18 years of age, Marques et al found AIP alterations in 6.8% of cases (23). In contrast, in a Spanish cohort of 235 apparently sporadic adenomas in patients ≤30 years of age, pathogenic AIPvar were detected in 3.8 of cases (24). The higher incidence of pathogenic mutations in some of the above-mentioned studies is mainly because the pediatric population was not included in our analysis.…”
Section: Discussionmentioning
confidence: 95%